A comparison study of some control methods for delta spatial parallel robot - Khang, Nguyen Van; Hoang, Nguyen Quang; Sang, Nguyen Duc; Dung, Nguyen Dinh (Journal of Computer Science and Cybernetics, 2015)
A comparison between three methods applied to parallel robot control namely: computed torque controller, sliding mode control and sliding mode control using neural networks is presented in this paper. The simulation results show that PD control method is only accurate when model parameters are precisely identified. In case of uncertain parameters, sliding mode and neural network sliding mode control methods are applied instead. Three controllers are implemented in Matlab for simulation. The results show that the control quality is improved by using the neural network sliding mode control method in comparison with two others.